Klastering Industri Kecil Dan Menengah Di Kecamatan Gebog Kabupaten Kudus Menggunakan Sistem Informasi Geografis - Setiawan, Arif; Setiaji, Pratomo (Jurnal Sains dan Teknologi, 2014)
Research by title geographic information system clustering of small and medium industries in the sub district  gebog  Holy  done  in  order  to  provide  a  reference  to  the  Holy  District  Government  ,  in developing  small  and  medium  industries  in  the  district  Gebog .  Geographic  Information  System industry clustering in the district gebog mapped based on location , mapping industry in the district Gebok first step in the development of small and medium industries in all regions of the Holy , where the industry will be grouped based on the number of business units , total employment , and investment value . The method used in this study is to map the industry small and medium industries in the district area  Gebog  ,  the  data  used  in  this  study  is  the  data  Gebog  industry in  the  district  .  Bearing  and distance  retrieved  from  the  zero point is square  - the main  sanctuary .  The results  of  this  study is  a map  -based  information  systems  ,  and  displays  information  on  the  number  of  business  units  ,  the amount of labor and the value of the investment industry in the district gebog .